Associations of Physical Activity and Sedentary Time with Metabolic Syndrome in Saudi Adult Males - Aljuhani O; Alkahtani S; Alhussain M; Smith L; Habib SS (Dove Medical Press, 2020)
Osama Aljuhani,1 Shaea Alkahtani,2 Maha Alhussain,3 Lee Smith,4 Syed Shahid Habib5 1Department of Physical Education, College of Sport Sciences and Physical Activity, King Saud University, Riyadh 4545, Saudi Arabia; 2Department of Exercise Physiology, College of Sport Sciences and Physical Activity, King Saud University, Riyadh 4545, Saudi Arabia; 3Department of Nutrition and Food Sciences, College of Agricultural and Food Sciences, King Saud University, Riyadh, Saudi Arabia; 4The Cambridge Centre for Sport and Exercise Sciences, Anglia Ruskin University, Cambridge CB1 1PT, UK; 5Department of Physiology, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Osama AljuhaniCollege of Sport Sciences and Physical Activity, King Saud University, P.O. Box-1949, Riyadh 11441, Saudi ArabiaTel +966-556363500Email oaljuhani@ksu.edu.saPurpose: The association between objectively measured sedentary behavior and physical activity with metabolic syndrome (MetS) has been rarely investigated in Saudi Arabia. The purpose of the current study was to examine the association of objectively measured sedentary, light physical activity (LPA), and moderate-vigorous physical activity (MVPA) with MetS among Saudi adult males.Materials and Methods: The study participants were 103 males from Riyadh, Saudi Arabia (mean age = 54.9 ± 10.6 years). Metabolic syndrome was defined based on having three or more of cardiometabolic risk factors. Triaxial accelerometers were used to measure the time spent on sedentary and physical activities across 7 days. A minimum four days with ≥ 10 hours of wearing time per day were considered a valid data. Binary logistics regression models were performed to examine the association of sedentary and physical activity levels with MetS vs no MetS. Model 1 was unadjusted, models 2, 3, and 4 were mutually controlled for sedentary, light, and MVPA intensities.Results: About 38% of males in the present study were classified as having MetS as demonstrated by a significant (p< 0.05) decrease in high-density lipoprotein cholesterol (HDL-C) and a significant (p< 0.05) increase in body weight, body mass index (BMI), waist circumference (WC), systolic blood pressure, glucose, and triglycerides compared to those without MetS. In addition, low levels of LPA (less than 6.3 hours per day) were significantly associated with the risk of having MetS, independent of sedentary and MVPA (odds ratio (OR) 4.26– 6.96). The results showed that the associations between sedentary tertiles and MetS were not statistically significant. Levels of MVPA were also not significantly associated with an increased risk of developing MetS in all models.Conclusion: This study showed that low levels of LPA were significantly associated with the risk of having MetS in Saudi males from Riyadh city, independent of MVPA and sedentary time. The results suggest that future intervention studies should assess the positive effect of increasing levels of LPA in reducing the risk of developing MetS in males.Keywords: accelerometer, MetS, sedentary time, MVPA, light activity